2021
DOI: 10.1155/2021/4723092
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Glomerulotubular Nephritis as an Initial Presentation of a Lethal Diquat Ingestion

Abstract: Introduction. Diquat is an herbicide that can lead to rapid multiorgan system failure upon toxic ingestion. Although Diquat shares a similar chemical structure with paraquat, diquat is still readily available to the general population, and in contrast to paraquat, it is not regulated. We present a case of an intentional diquat poisoning which emphasizes the necessity of the early recognition due to atypical symptoms within the first 24 hours and certainly enhanced regulatory restrictions on this very toxic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
1
3
0
3
Order By: Relevance
“…Acute diquat poisoning damaged the kidney, liver, and central nervous systems, and subsequent multiple-organ failure syndromes were the main cause of death (3). Diquat poisoning caused acute kidney injury (AKI) as much as 73.3%, which was higher than other types of pesticide poisoning (4)(5)(6). Rhabdomyolysis is rarely reported in diquat poisoning (7,8), but it could largely aggravate kidney injury.…”
Section: Introductionmentioning
confidence: 99%
“…Acute diquat poisoning damaged the kidney, liver, and central nervous systems, and subsequent multiple-organ failure syndromes were the main cause of death (3). Diquat poisoning caused acute kidney injury (AKI) as much as 73.3%, which was higher than other types of pesticide poisoning (4)(5)(6). Rhabdomyolysis is rarely reported in diquat poisoning (7,8), but it could largely aggravate kidney injury.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that DQ is selectively toxic to the kidneys, and has a similar chemical structure to that of the highly nephrotoxic orellanine [ 2 ]. Renal tubular dysfunction is the initial manifestation of DQ toxicity [ 3 ], and obvious renal tubular epithelial cell damage has been observed during autopsy [ 4 ]. The offspring of DQ-intoxicated rats exhibit renal duct damage.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 Several case reports showed that acute high-dose DQ poisoning usually affected the kidneys, liver, brain, and heart. 11 , 12 , 13 , 14 Current toxicology studies indicate that DQ does not covalently bind to macromolecules (i.e., lipids, proteins and nucleic acids), but it can generate reactive oxygen species (ROS) in cells through an oxidation–reduction cycle process, resulting in increased phospholipid membrane permeability and subsequent cell membrane rupture. 5 Recent research has shown that lethal DQ poisoning can cause central nervous system injury, as evidenced by variable CT imaging, including cerebral ischaemia, cerebral haemorrhage, and brain swelling.…”
Section: Introductionmentioning
confidence: 99%